Strand-swapped SH3 domain dimer with superoxide dismutase activity - Häge, Florian; Schwan, Merlin; Conde González, Marcos Rafael; Huber, Jonas; Germer, Stefan; Macrì, Matilde; Kopp, Jürgen; Sinning, Irmgard; Thomas, Franziska (ACS central science, 2025)
The design of metalloproteins allows us to better understand metal complexation in proteins and the resulting function. In this study, we incorporated a Cu2+-binding site into a natural protein domain, the 58 amino acid c-Crk-SH3, to create a miniaturized superoxide dismutase model, termed SO1. The resulting low complexity metalloprotein was characterized for structure and function by circular dichroism and UV spectroscopy as well as EPR spectroscopy and X-ray crystallography. The miniprotein was found to be a strand-swapped dimer with an unusual coupled binuclear Type 2-like copper center in each protomer. SO1-Cu was found to be SOD-active with an activity only 1 order of magnitude lower than that of natural SOD enzymes and 1 to 2 orders of magnitude higher than that of other low-complexity SOD protein models of similar size. This serendipitous design provides us with a new structural template for future designs of binuclear metalloproteins with different metal ions and functions.
Gesehen am 12.09.2025